2021
DOI: 10.2142/biophysico.bppb-v18.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-pressure treatment on the structure and function of myofibrils

Abstract: The effects of high pressure (40–70 MPa) on the structure and function of myofibrils were investigated by high pressure microscopy. When this pressure was applied to myofibrils immersed in relaxing solution, the sarcomere length remained almost unchanged, and the A band became shorter and wider. The higher the applied pressure, the faster the change. However, shortening and widening of the A band were not observed when pressure was applied to myofibrils immersed in a solution obtained by omitting ATP from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The procedure for preparing myofibrils from rabbit psoas muscle was approved by the Institutional Animal Care and Use Ethical Committee of Waseda University and followed the Waseda University animal experimentation rules [ 16 ]. Experiments using myofibrils were approved by the Institutional Animal Care and Use Ethical Committees of Waseda University and the University of Tokyo [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure for preparing myofibrils from rabbit psoas muscle was approved by the Institutional Animal Care and Use Ethical Committee of Waseda University and followed the Waseda University animal experimentation rules [ 16 ]. Experiments using myofibrils were approved by the Institutional Animal Care and Use Ethical Committees of Waseda University and the University of Tokyo [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The procedure for preparing myofibrils from rabbit psoas muscle was approved by the Institutional Animal Care and Use Ethical Committee of Waseda University and followed the Waseda University animal experimentation rules [ 16 ]. Experiments using myofibrils were approved by the Institutional Animal Care and Use Ethical Committees of Waseda University and the University of Tokyo [ 16 ]. Myofibrils were obtained from the intestinal psoas muscle of male Japanese White (JW) rabbits (2.5–3.0 kg, conventional) decapitated after anesthesia induced by injection of 25 mg/kg sodium pentobarbital into the ear vein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cardiac muscle percentage increment of the oxygen consumption/concentration 16 relation is correlative with its basic metabolic rate. The muscle lengthening stretch enhances the oxygen consumption and the metabolic rate (Figure 13) [72] .…”
Section: The Instantaneous Energy Consumption In the Muscle Fiber Tol...mentioning
confidence: 99%
“…It has been reported that sarcomere becomes an oscillation state that repeats contraction and relaxation under a solution with intermediate conditions between contraction and relaxation ( Fabiato and Fabiato, 1978 ; Okamura and Ishiwata, 1988 ; Linke et al, 1993 ; Sasaki et al, 2006 ; Shintani et al, 2014 ; Shintani, 2021 ). Details are given in the cited paper, but “intermediate conditions between contraction and relaxation” are solution conditions in which sarcomere can exert a contractile force of about half of the maximum contractile force.…”
mentioning
confidence: 99%